On the variability in fracture toughness of 'ductile' bulk metallic glasses. (June 2015) - Narayan, R.L.; Tandaiya, Parag; Garrett, G.R.; Demetriou, M.D.; Ramamurty, U.
Abstract : The mode I fracture toughness, K Ic, of ductile bulk metallic glasses (BMGs) exhibits a high degree of specimen-to-specimen variability. By conducting fracture experiments in modes I and II, we demonstrate that the observed high variability in mode I, vis-à-vis mode II, is a result of highly variable propensity for the conversion of shear bands into cracks in mode I whereas in mode II, crack growth direction is fixed. Thus, the measured variability in K Ic is intrinsic to the nature of BMGs.